The Potential of Vegan Leathers in Sustainable Accessory Design: An Experimental Approach - Çakar, Özlem Aybüke; Eroğlu, Nilşen Sünter (Universitas Komputer Indonesia, 2025)
This study examines the sustainability advantages of plant-based vegan leather materials compared to traditional animal leathers and explores the current applications of leather-like vegan surfaces in the production of accessories such as bags, keychains, and wallets. Various types of plant-based vegan leather, which are widely used in sectors such as fashion, automotive, interior design, and accessory design, have been comprehensively evaluated. As part of the research, accessory designs were developed using commercially sourced rubber-based vegan leather. The same model was also produced using synthetic leather. In addition, vegan leather-like surfaces were produced at home using natural and recyclable materials such as capsule coffee grounds, pineapple leaves, and peanut shells, all considered organic waste. Among these, the coffee-based surfaces particularly those made from used capsule coffee grounds were used to design and manufacture accessory prototypes such as bags and wallets. The entire design process was conducted digitally using Adobe Illustrator, and the prototypes were carefully prepared and modeled in digital format. This study aims to offer an innovative and practice-oriented approach for designers, producers, and researchers working in the field of sustainable accessory design, through the use of both commercial and home-produced alternative materials. The findings are expected to contribute to the literature on sustainable fashion and the development of alternative materials. Keywords: Vegan leather, Sustainable fashion, Accessory design, Bio-based materials, Material innovation